What is the role of technology in improving patient safety? A French, German and UK healthcare professional perspective. Issue 6 (December 2020) - Astier, Alain; Carlet, Jean; Hoppe-Tichy, Torsten; Jacklin, Ann; Jeanes, Annette; McManus, Steve; Pletz, Mathias W; Seifert, Harald; Fitzpatrick, Ray
Patient safety in hospitals can be compromised by preventable adverse events (AE). Among the preventable AEs, hospital-acquired infections (HAIs) are one of the most burdensome, contributing to not only poorer patient outcomes but institutional burden through direct financial losses and increased patient length of stay. Technological innovations can enhance patient safety by automating tasks, introducing medication alerts, clinical reminders, improved diagnostic and consultation reports, facilitating information sharing, improving clinical decision-making, intercepting potential errors, reducing variation in practice, and managing workforce shortages as well as making complete patient data available. A multidisciplinary working group from three European countries was convened to discuss how to optimise the use of technology to reduce preventable AEs in acute care hospitals. The working group identified examples where they felt there were opportunities to streamline patient pathways, including antimicrobial stewardship, point of care testing, microbiology test reporting to streamline time from sample-taking to clinical decision and mobile automated dispensing systems, which can reduce the burden on overworked staff. The working group also discussed key factors that were critical to ensuring different stakeholders, both within and outside the hospital, could meaningfully contribute to improving patient safety. They agreed that technological approaches and advances would have limited impact without meaningful cultural changes at all levels of healthcare infrastructure to implement the benefits offered by current or future technologies.